(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
The questions o f assessment and prédiction of potential charnels o f infiltration of radionuclides in géologie environment are discussed. This is specially important for underground allocation of the nuclear objects. The method of allows for spatial-temporal variations in a geological massif at ail hierarchical levels from régional tectonic processes up top peri-contour zones of chambers.